Chadian Sister Engages Kansas City Youth about Peace and Justice - Londadjim, Nelkem Jeannette (Book collections on Project MUSE., 2020)
A woman meets young people from various backgrounds - at a U.S. university. She is African, from Chad. The students, eager to learn about her life, ask probing questions. She tells them about the war, her flight, her refugee status, her experiences in West Africa and Algeria. In turn, she discovers that they are still exposed to racism in their country - an outrage compounded by the murders of George Floyd and Breonna Taylor. As an activist in residence, she dialogues with the students about their aspirations and encourages them to become artisans of peace and justice. We look forward, in turn, to the thoughts and writings of young people about the encounters shared here and the illustrations by a young Kenyan woman that accompany the essays.